Asymmetric Supercapacitors Based on Hierarchically Nanoporous Carbon and ZnCo2O4 From a Single Biometallic Metal-Organic Frameworks (Zn/Co-MOF) - He, Da; Gao, Yu; Yao, Yucen; Wu, Ling; Zhang, Jiang; Huang, Zheng-Hong; Wang, Ming-Xi (Frontiers in Chemistry, 2020)
Metal-organic framework (MOF)-derived nanoporous carbons (NPCs) and porous metal oxide nanostructures or nanocomposites have gathered considerable interest due to their potential use in supercapacitor (SCs) applications, owing to their precise control over porous architectures, pore volumes, and surface area. Bimetallic MOFs could provide rich redox reactions deriving from improved charge transfer between different metal ions, so their supercapacitor performance could be further greatly enhanced. In this study, “One-for-All” strategy is adopted to synthesize both positive and negative electrodes for hybrid asymmetric SCs (ASCs) from a single bimetallic MOF. The bimetallic Zn/Co-MOF with cuboid-like structures were synthesized by a simple method. The MOF-derived nanoporous carbons (NPC) were then obtained by post-heat treatment of the as-synthesized Zn/Co-MOF and rinsing with HCl, and bimetallic oxides (ZnCo2O4) were achieved by sintering the Zn/Co-MOF in air. The as-prepared MOF-derived NPC and bimetallic oxides were utilized as negative and positive materials to assemble hybrid ASCs with 6 M KOH as an electrolyte. Owing to the matchable voltage window and specific capacitance between the negative (NPC) and positive (ZnCo2O4), the as-assembled ASCs delivered high specific capacitance of 94.4 F/g (cell), excellent energy density of 28.6 Wh/kg at a power density of 100 W/kg, and high cycling stability of 87.2% after 5,000 charge-discharge cycles. This strategy is promising in producing high-energy-density electrode materials in supercapacitors.